The Effect of Positive Thinking Training in Increasing Self-Confidence in Students - Belly Lestari; Ade Irma Oktiyani; Resky Ramadhani; Muhammad Naufal Lutfhi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
This research aims to determine the effect of positive thinking training in increasing self-confidence in UIGM students class 2020-2022. This research is a quantitative experimental research with a one group pretest- posttest design. The variable measured is increasing self-confidence in UIGM students class 2020-2022. The data collection process in this study was measured twice within 7 days. The population in this study were UIGM students class 2020-2022. The sample used was 20 people. In this study, the t-test or Mann-Whitney U test was used to see the level of self-confidence. Descriptive statistics show that the pretest score has an average of 47.33 and the posttest score has an average of 27.67. The normality test shows that the data is normally distributed. Paired Samples Test is used to see the significance between posttest and pretest scores, and shows that positive thinking training has a positive effect on increasing the self-confidence of UIGM students class of 2020-2022